Internal Mobility in Italy: A New Delay - Cecilia Reynaud; Enrico Tucci (Stanovništvo)
From the second half of the 1990s, mobility appears to have changed profoundly from the great migrations of the 1960s, for two main reasons: firstly, the rise in short-range mobility; and secondly, the strong increase in attraction by geographical areas in Central and above all North-eastern Italy. In more recent years, the evolution of internal mobility has changed again, with a further fall coupled with a loss of attractiveness for some Central and Northern areas.